Current analysis of orcharding in the Isparta Province (Turkey) - Sargin Sevil; Okudum Ramazan (Bulletin of Geography. Socio-Economic Series, 2014)
In this study, orcharding activity in the Isparta Province, Turkey, is analysed. Until a few years ago, the economy of Isparta was associated with hand carpet weaving, rose-growing and rose-oil extraction. However, over the last few years orcharding has attracted attention as the most important economic activity in Isparta. This is especially visible in the districts of Eğirdir, Gelendost, Senirkent and Yalvac where many kinds of fruits, specifically apples and cherries, are grown for the market. Physical geography features of Isparta have an important potential for developing orcharding. Suitable climatic conditions, fertile soils and fresh water resources, both surface and underground, are distinctive elements of this potential. In addition, irrigation projects, modern agricultural techniques, quality and resistible fruit types, appropriate fertilisation, pruning and disinfecting are human activities effecting the development of orcharding. Moreover, establishing modern and high capacity cold stores nearby the areas where fruits are grown is regarded an important factor increasing the value of Isparta fruits on the national and international markets. Thus, developing commercial orcharding in Isparta is gaining importance as a profitable activity as well as an opportunity for rural population for employment in fruit picking, storing, packaging and transporting. The emphasis of this study is put on current development of orcharding, distribution of apple, cherry, grape and other fruits production, reasons for this distribution and problems associated with orcharding in Isparta. Besides formal data collection, the findings obtained during field studies in Boğazova as well as on the Uluborlu-Senirkent and Gelendost Plains enable the authors to conclude that orcharding has become the most important rural activity in the region.